Regulatory effects on short-term interest rates - Ranaldo, Angelo; Schaffner, Patrick; Vasios, Michalis (Journal of Financial Economics, 2021)
We analyze the effects of prudential regulation on short-term interest rates. The European Market Infrastructure Regulation (EMIR) induces clearing houses (CCPs) to supply large amounts of cash in reverse repurchase agreements (repos). Basel III, in contrast, disincentivizes the borrowing demand by tightening banks’ balance sheet constraints. Using unique regulatory data of CCP investment activity and repo transactions, we find compelling evidence for both the supply and demand channels. The overall effects are decreasing short-term rates and increasing market imbalances in various forms, all of which entail unintended consequences due to the new regulatory framework.